Perancangan Sistem Informasi Jalur Angkot di Kabupaten Garut Berbasis Webiste - Asep Deddy Supriatna; Raden Erwin Gunadhi Rahayu; Lendra Lendra (Institut Teknologi Garut, 2022)
Angkot is a mode of public transportation that can be used by the public at large, one of which is the city of Garut which has several public transportation routes that have been determined by the local government. With so many angkot routes or routes spread to various locations, it should make it easier for the public to find detailed information about angkot information. However, because of the limited information available, people still have difficulty finding information about the angkot they want to take. Given these problems, the purpose of this research is to design a webiste-based information system for angkot routes in Garut Regency. As an alternative solution to assist the public in getting information about public transportation easily, quickly and precisely, without having to come to the terminal or to the relevant offices that manage the operation of public transportation. The method used in this study is a rational unified process consisting of four stages. Among them, inception, elaboration, construction, and transition, then for modeling using a unified modeling language. For testing this application using black box testing. The results of this study can be concluded that the website-based information system application for angkot routes in Garut Regency, which has a feature in the form of angkot route maps, makes it easy for the public to get detailed information about angkot.